2012
DOI: 10.1111/j.1399-3046.2012.01781.x
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immunity is involved in the development of pericentral fibrosis after pediatric live donor liver transplantation

Abstract: Although LT can be successful for treating end-stage liver disease in children, some patients develop fibrosis around the central vein area (PCF). This raises the possibility that PCF could lead to later cirrhosis and graft failure. Here, we report a retrospective immunohistochemical study of 28 patients who received a live donor liver transplant. We assessed the incidence and etiology of PCF using CD3, CD20, HLA-DR, and C4d-specific antibodies. Histological evidence of PCF was found in 13 cases (46.4%), of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 32 publications
2
38
1
1
Order By: Relevance
“…4,5,24,25 Our pediatric study population was examined using a single antigen assay with Luminex beads; 68% of patients with histological signs of chronic rejection and the necessity of retransplantation exhibited high levels of DSA with this method. This is a higher rate than in our patients with an 26 Their results suggest that there is also an influence of DSA on the development of pericentral fibrosis. In our pediatric study cohort, we found no difference between DSA+ ve and DSA− ve patients with chronic rejection with regard to histological findings, such as biliary lesions, signs of cholestasis, or vascular rejection, as well as fibrosis or cirrhosis.…”
Section: Discussioncontrasting
confidence: 72%
“…4,5,24,25 Our pediatric study population was examined using a single antigen assay with Luminex beads; 68% of patients with histological signs of chronic rejection and the necessity of retransplantation exhibited high levels of DSA with this method. This is a higher rate than in our patients with an 26 Their results suggest that there is also an influence of DSA on the development of pericentral fibrosis. In our pediatric study cohort, we found no difference between DSA+ ve and DSA− ve patients with chronic rejection with regard to histological findings, such as biliary lesions, signs of cholestasis, or vascular rejection, as well as fibrosis or cirrhosis.…”
Section: Discussioncontrasting
confidence: 72%
“…2) Lower class II expression might affect downstream effector mechanisms and instead of “capillaritis”, DSA might trigger endothelial cell phenotype changes and/or activation of pathways that promote or retard cellular inflammation, coagulation, apoptosis and complement deposition[31,32,75-78,80-83]. 3) Direct activation of stellate cells is possible given the strong empiric association between DSA and non-inflammatory fibrosis[62,104,105]. …”
Section: Acute Antibody - Mediated Rejectionmentioning
confidence: 99%
“…Histopathological changes observed were either directly or indirectly attributed to IS minimization[104,130,131] and associated with DSA, especially class II DSA, endothelial and stromal C4d, and CD20+ perivenular infiltrates[104]. Peribiliary plexus capillary and sinusoidal endothelial cell HLA-DR upregulation was spatially linked with nearby inflammation, which was most prominent in patients with co-existent TCMR with or without perivenular fibrosis[105]. Re-institution or increasing immunosuppression decreased C4d deposits and stabilized or reversed perivenular fibrosis[131].…”
Section: Chronic Antibody-mediated Injurymentioning
confidence: 99%
“…60 Interestingly, centrilobular (perivenular) fibrosis in late biopsies (>5 years after transplantation) is not uncommon for pediatric LDLT recipients with circulating DSAs, and it may be reversible through an increase in immunosuppression. 25,61,62 If this mechanism of action is indeed effective, then extra caution must be observed for recipients who are enrolled in immunosuppression minimization or withdrawal trials. In a retrospective review of patients who had been off immunosuppression, those with circulating DSAs were found to be more likely to develop rejection.…”
Section: Possible Mechanism Of Donor-specific Human Leukocyte Antigenmentioning
confidence: 99%